2022
DOI: 10.3389/fnmol.2022.926928
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomal MiRNAs Promote M2 Macrophages Polarization: Therapeutic Opportunities for Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is an enormous public health concern affecting approximately 250,000–500,000 people worldwide each year. It is mostly irreversible considering the limitations of currently available treatments, and its prevention and management have been the prime focus of many studies. Mesenchymal stem cell (MSC) transplantation is one of the most promising treatments for SCI. The role of MSCs in SCI has been studied extensively, and MSCs have been shown to have many limitations. Moreover, the therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 87 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…A well-established mechanism through which MSCs-sEVs exert immunomodulation is by influencing macrophage polarization [18]. Recent evidence has suggested that MSCs & their EVs undergo efferocytosis via engulfment by macrophages, thereby instructing their polarization [32][33][34]. These EVs are acknowledged for transporting a multitude of miRNAs that contribute to directing macrophage polarization towards the M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-established mechanism through which MSCs-sEVs exert immunomodulation is by influencing macrophage polarization [18]. Recent evidence has suggested that MSCs & their EVs undergo efferocytosis via engulfment by macrophages, thereby instructing their polarization [32][33][34]. These EVs are acknowledged for transporting a multitude of miRNAs that contribute to directing macrophage polarization towards the M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Since MSCs are widely recognised for their immunomodulatory properties, we sought to evaluate the efficacy of these sEVs in polarization of macrophages, efferocytotic activity, T-Cell Proliferation, as well T-Regulatory cells induction [18,[32][33][34][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of let-7a-5p suppresses the MAPK/ERK signaling pathway [59,60]. Additionally, MSC exosomes have promoted M2-like macrophage polarization, possibly through the transfer of axosomal miRNAs and activation of AKT-dependent signaling pathways via adenosine receptors A2A and A2B [61][62][63][64]. Thus, EV-let-7a-5p provide a dual advantage by simultaneously suppressing the MAPK-mediated regulation of STAT3 phosphorylation and activating the AKT pathway, which can be improved to influence macrophage polarization and modulate the inflammatory immune response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, suppressing inflammation using MSC-EVs that target the activation of nuclear factor-κB (NF-κB) signaling and microglial complement system promoted axon regeneration and functional recovery after SCI [ 188 ]. Likewise, various miRNAs secreted by MSC-EVs, such as miR-21-5p, miR-182 and let-7b, which polarise macrophages towards the anti-inflammatory M2 phenotype, can alleviate inflammation mediated by toll-like signaling and promote axon regeneration and functional recovery [ 189 , 190 , 191 ]. The recruitment of macrophages from the peripheral circulation in response to vascular damage further exacerbates inflammation and is detrimental to axon regeneration, thus making it an important target after SCI [ 192 ].…”
Section: Stem Cell-based Evs and Nerve Regenerationmentioning
confidence: 99%